Językowy obraz świata w nazwach odzieży (na materiale dialektów północnoruskich) - Kryłowa, Olga (Studia Rossica Posnaniensia, 2010)
In the article lexical units of a lexical set “Clothes” are regarded. Attempt to reveal the motivation attributes put into the basis of nominations is undertaken, and to interpret them as display of language consciousness of dialect owners. Observing the names of women's clothes shows that local tinge and specificity of the same lexico-semantic group in the Russian dialectal system is attained by various combinations of many components: motivating features, nomination means, motivation basis. Semantic specificity of some lexical groups including the group of women's clothes names is shown first of all in particular qualities of their nomination: in connection of motivating features with a certain group, in using different motivating features for naming the same object or the same motivating feature for naming different objects.